Two dimensional car body visualization using air flow bench - Mohamad Al Rassid, Mohamad Borhanudin (2008)
In the automotive industry which is now very fast-paced, the production of the variety of cars have resulted that owning a car has become a necessary asset in life. More demands for cars have made most automotive companies to make a huge sale of their products. Therefore, more car makers are in the dilemma of tough competition to produce good cars in terms of shapes, capacity and horsepower. Hence, Engineers in this field have been fighting hard to come up with new creations of hybrid cars at the same with aerodynamic looks. Eventually, tests will be conducted to achieve these aerodynamic cars. The use of “air flow bench” has been carried out to ensure it meets the aerodynamic criteria. In this project, it shows how all car models is being tested and how this “air flow bench” works. In conclusion, the project timeline has been met to the schedule and is in smooth operation.